2013
DOI: 10.1016/j.stem.2013.04.026
|View full text |Cite|
|
Sign up to set email alerts
|

KDR Identifies a Conserved Human and Murine Hepatic Progenitor and Instructs Early Liver Development

Abstract: SUMMARY Understanding the fetal hepatic niche is essential for optimizing the generation of functional hepatocyte-like (hepatic) cells from human embryonic stem cells (hESCs). Here, we show that KDR (VEGFR2), previously assumed to be mostly restricted to mesodermal lineages, marks a hESC-derived hepatic progenitor. hESC-derived endoderm cells do not express KDR, but when cultured in media supporting hepatic differentiation, generate KDR+ hepatic progenitors and KDR- hepatic cells. KDR+ progenitors require acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 55 publications
4
60
0
Order By: Relevance
“…All these KDR+ progenitors are of mesodermal origin. Our previous study provided the first evidence for the existence of a KDR+ progenitor for liver, an endoderm derivative (Goldman et al., 2013). Given the well-documented studies on the bipotentiality of a KDR+ progenitor for the EC lineage and mesodermal derivatives, it should perhaps not be surprising that we were able to document the bipotentiality of an endoderm-derived KDR+ progenitor for hepatic endoderm cells and ECs using clonal assays.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…All these KDR+ progenitors are of mesodermal origin. Our previous study provided the first evidence for the existence of a KDR+ progenitor for liver, an endoderm derivative (Goldman et al., 2013). Given the well-documented studies on the bipotentiality of a KDR+ progenitor for the EC lineage and mesodermal derivatives, it should perhaps not be surprising that we were able to document the bipotentiality of an endoderm-derived KDR+ progenitor for hepatic endoderm cells and ECs using clonal assays.…”
Section: Discussionmentioning
confidence: 98%
“…Our previous work revealed the existence of KDR-expressing hepatic progenitors (KDR+ progenitor) in human embryonic stem cell (hESC) cultures differentiated toward the hepatic lineage (Goldman et al., 2013). Isolated hESC-derived endoderm cells give rise to both the KDR+ hepatic progenitors and the committed KDR− hepatic cells.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely reported that hepatocytes can be derived from embryonic stem cells, mesenchymal stem cells, and iPS cells [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28]. While these progenitor/stem cells are potentially important sources for hepatocyte transplantation, the lineage-specificity and differentiation efficiency of these progenitor cells remain to be fully characterized in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…This matter is further complicated by our current lack of the knowledge and understanding of the detailed mechanism through which hepatic progenitors are regulated and directed to hepatocyte lineage-specific differentiation. Thus, liver progenitor cells isolated from both fetal and adult liver tissues should have the inherited advantages over those extrahepatic sources of stem cells [1,21,29,30,31,32,33,34,35,36]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation